Case Report: Expanding the ocular horizon: subperiosteal orbital hematoma and Roth spots in known case of sickle cell disease - Patil, Rajvardhan Ravindra; Acharya, Sourya; Karwa, Vineet; Dhondge, Rushikesh; Shaikh, Suhail; Kothari, Manjeet (Frontiers in Hematology, 2025)
Sickle cell disease is a prevalent haemoglobinopathy that is hereditary. People with sickle cell disease frequently experience vaso-occlusive crises, which lead to substantial morbidity from end-organ ischaemia and infarction. Numerous organs, including the bones, brain, lungs, spleen, retina, and penis, may be affected. As a result, symptoms may include painful bone crises, cerebrovascular accidents, acute chest syndrome, sequestration crises, retinal haemorrhage, and priapism. In sickle cell disease, subperiosteal orbital haemorrhage is a rare vaso-occlusive crisis (VOC). Roth spots (white-centred, flame-shaped retinal haemorrhages), occurring commonly in subacute bacterial endocarditis, can also be seen in leukaemia, pre-eclampsia, and hypertensive retinopathy. A 19-year-old male patient with sickle cell disease (HbSS) presented to the hospital with ptosis and swelling in his right periorbital region 3 days after being brought to the hospital for a sickle cell crisis. It was later determined to be an acute subperiosteal orbital hematoma along with Roth spots, an uncommon clinical manifestation of sickle cell disease, only after a thorough clinical and radiological assessment.